CHARACTERISTICS OF A POORLY-GRADED SAND COMPACTED BY THE GYRATORY AND MODIFIED PROCTOR PROCEDURE - Badruzaman, Dadan
CHARACTERISTICS OF A POORLY GRADED SAND COMPACTED BY THE GYRATORY AND MODIFIED PROCTOR PROCEDURES, Dadan Badruzaman, 2000, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. This thesis describes a study of the influence of method of compaction on the compaction and strength characteristics of a soil taken from a location between Negerisakti and Rajabasa in the Lampung Province. The soil will be used as the subgrade for a new road connecting these two villages. The soil, classified in the USCS as SP (poorly-graded sand), was compacted by impact (Modified Proctor) and Gyratory procedures. Variation in compactive effort was achieved in the case of the former by varying the number of hammer blows (25, 41, 56, 71) and in the case of the latter by varying the vertical stress (500 kPa, 700 kPa), the angle of gyration (1Â°, 1.250) and the number of gyrations (50, 75, 100). Increasing the number of blows in impact compaction resulted in an increase in maximum dry density (MDD) and a reduction in the corresponding optimum moisture content (OMC); strength as indicated by California Bearing Ratio (CBR) also increased. The influence of the three parameters controlling compactive effort in Gyratory compaction was found to be interactive. For example the influence of the number of gyrations on MDD was more significant at the lower value of vertical stress; the influence of angle of gyration on MDD reduced as the number of gyrations and/or vertical stress increased